A Study of the Reflection of Qur'anic Verses in Mihrab Carpets of the Safavid Period - Elaheh Panjahbashi; Rana Mohammadzadeh (قرآن فرهنگ و تمدن, 2025)
Among the significant decorative elements in Safavid carpets-representing a fusion of Islamic art and culture-is the use of inscriptions containing Qur’anic verses, poetry, or supplications. Mihrab-design carpets, in particular, were commonly adorned with Qur’anic inscriptions and functioned as prayer rugs. In such cases, Qur’anic verses were not merely ornamental but conveyed religious meaning. This article examines how Islamic concepts—especially the content of Āyat al-Kursī-are manifested in the inscriptions of two selected mihrab carpets from the Safavid period. It aims to explore the relationship between the Qur’anic content of the inscriptions and the arabesque motifs and mihrab designs. The study addresses two main questions: What are the formal and semantic features of the woven inscriptions in these carpet bands? And how do the inscriptions relate to the visual motifs and designs? Relying on library sources and image analysis, and using a historical-descriptive method, the research finds that the content of the inscriptions-such as specific verses and dhikr formulas-functions in harmony with the architectural and floral elements of the mihrab-shaped carpets. This confluence of sacred text and design showcases the unity of Islamic art and faith, turning the carpets into a manifestation of Qur’anic meaning.